Changes in the Chemical and Physical Properties of Paper Documents due to Natural Ageing - Čabalová, Iveta; Kačík, František; Gojný, Jan; Češek, Břetislav; Milichovský, Miloslav; Mikala, Ondřej; Tribulová, Tereza; Ďurkovič, Jaroslav (My University, 2017)
The aim of this study was to assess the changes in chemical and physical properties of selected paper documents, dating from the 18th century to the present date.
Změny chemických a fyzikálních vlastností papírových dokumentů během přirozeného stárnutí
Keywords: paper documents; natural ageing; pH; formic acid; acetic acid; fibre length; holocellulose; papírové dokumenty; přirozené stárnutí; pH; kyselina mravenčí; kyselina octová; délka vláken; holocelulóza